A Photoswitchable Agonist for the Histamine H3 Receptor, a Prototypic Family A G‐Protein‐Coupled Receptor. (27th February 2019) - Hauwert, Niels J.; Mocking, Tamara A. M.; Da Costa Pereira, Daniel; Lion, Ken; Huppelschoten, Yara; Vischer, Henry F.; De Esch, Iwan J. P.; Wijtmans, Maikel; Leurs, Rob
Abstract: Spatiotemporal control over biochemical signaling processes involving G protein‐coupled receptors (GPCRs) is highly desired for dissecting their complex intracellular signaling. We developed sixteen photoswitchable ligands for the human histamine H3 receptor (hH3 R). Upon illumination, key compound 65 decreases its affinity for the hH3 R by 8.5‐fold and its potency in hH3 R‐mediated Gi protein activation by over 20‐fold, with the trans and cis isomer both acting as full agonist. In real‐time two‐electrode voltage clamp experiments in Xenopus oocytes, 65 shows rapid light‐induced modulation of hH3 R activity. Ligand 65 shows good binding selectivity amongst the histamine receptor subfamily and has good photolytic stability. In all, 65 (VUF15000) is the first photoswitchable GPCR agonist confirmed to be modulated through its affinity and potency upon photoswitching while maintaining its intrinsic activity, rendering it a new chemical biology tool for spatiotemporal control of GPCR activation. Abstract : G‐Protein‐gekoppelte Rezeptoraktivierung : VUF15000 ist ein photoschaltbarer Agonist des Histamin‐H3 ‐Rezeptors, der eine vollständige Aktivierung des Gi ‐Proteins sowohl für sein trans ‐ als auch für sein cis ‐Isomer bewirkt. In elektrophysiologischen Experimenten zeigt es zudem eine dynamische optische Modulation des H3 ‐Rezeptors. VUF15000 kann als photochrome Verbindung dabei helfen, die H3 ‐Rezeptor‐Signalkaskade mit raumzeitlicher Präzision aufzuklären.